Social policy, employment and family change in comparative perspective - Bradshaw Jonathan; Hatland Aksel (Cheltenham Edward Elgar, 2006)
This book is a comparative study of family change, parental employment and social policy in the five Nordic countries, the Netherlands, Germany and the United Kingdom. In all these countries family forms have been profoundly affected by lower fertility r
Keywords: Northern Europe,Families>Work and family>Social policy>